EFFECT OF LAND USE ON SPATIAL AND SEASONAL VARIATION OF WATER QUALITY IN CILIWUNG RIVER, WEST JAVA-INDONESIA - Eleonora Runtunuwu; Akihiko Kondoh; Kasdi Subagyono (JURNAL RISET GEOLOGI DAN PERTAMBANGAN, 2010)
ABSTRACT Study on water quality aspects of Ciliwung river has been conducted from January 2008 to November 2009 to address the impact of land use change on its seasonal variation.  Nitrogen compound of NO2 and NH4 were monitored along the Ciliwung river with different time.  Land use change within the Ciliwung watershed was analyzed using remote sensing data and correlate with NO2, NO3, NH4 concentration, conductivity and pH along the river.   The results showed that in area with higher populated areas such as found in the middle and downstream area of Ciliwung watershed, NO3 concentration is higher.  This obvious variation was also observed for conductivity and pH.  It was also observed that the more dense area as in the middle and downstream area the change of land use was obvious.  The NO3 concentration is much influenced by land use and vegetation change prior to human activity.  In general, NO3 observed on October 2008 was higher compared with that observed on January, April and July 2008. In October where it is rainy season, flushing of NO3 is higher and it was transported into the Ciliwung river.  The temporal variation is seemed to be due to variation of rainfall generating different runoff and nutrient flushing surrounding river.